Perception on Tourism Infrastructure available in Kanyam, Ilam Located in Eastern Nepal - Shree, Bishista; Kaini, Tika Raj (NUTA Journal, 2021)
Tourism infrastructure is the key to tourism development and one of the major factors for determining tourist satisfaction. Therefore, this paper examines the tourism infrastructure and tourist satisfaction in Kanyam of Ilam district in Nepal. Tourism infrastructure involves accommodation and other basic services like information, communication facilities. Kanyam is emerging as a popular tourist destination due to its felicitous tea garden and its prepossessing views. This study conducted the data through a survey with 70 articulated respondents comprising local people including intellectuals and elected representatives, tourism visitors, and tourists in the study area. The study result that more than 70 % of respondents think lack of infrastructure is a hindrance in tourism development. It can also be linked with the satisfaction among tourists underrated on accommodation services and sanitation services. This may be due to a lack of proper training for the tourism industry enterprisers. Further, the information service at the destination is not well established to inform at the destination. Despite this 80% of people involved in the tourism business were satisfied with the business as it is supporting the local economy and promotion of local products. Therefore, a master plan should be developed a master plan for infrastructure development for maintaining its image and bringing tourists back to the town.